Peran Media Sosial dalam Pelajaran IPS Kelas V di MI Ma’arif NU 1 Ajibarang Wetan - Hayati, Fika Husna; Ningsih, Tutuk (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Increasingly sophisticated technology must be balanced with its utilization in the world of education so as not to be left behind. In learning social studies students can train their social sensitivity, and teachers should be able to utilize the use of social media on students who can be diverted social media can be used as a source of student learning, especially in social studies learning. This study aims to identify the role of social media in social studies learning in class V MI Ma'arif NU 1 Ajibarang Wetan. The data is presented in the form of text narration. Sources of research data are obtained in three ways in the form of observation, interviews, and documentation. The data analysis technique uses three stages, as follows: data reduction, presentation of data obtained, and concluding the data. The result of this research is that social media has an important role in social studies learning. Social media has become a communication tool between madrasah, teachers, parents, madrasah committees, and students. On the other hand, WhatsApp, Instagram, and YouTube can facilitate access to learning resources, increase learning motivation, and provide access to material that has not been experienced directly by students. Teachers need to be responsive in using social media in social studies learning for students, because students still need assistance and supervision in accessing social media, especially regarding social media ethics.